The new faces of Christianity : believing the Bible in the global south - Jenkins, Philip, 1952- (Oxford ; New York : Oxford University Press, 2006)
Christianity is growing so rapidly in the global South that soon Africa may be home to the world's largest Christian population. But what sort of Christianity will that be? In Africa, Asia, and Latin America, Christians live in settings very close to the social, cultural, and intellectual milieu in which the New Testament itself was written. For this reason, Philip Jenkins argues, they read the Scriptures with a freshness and authenticity impossible in the prosperous societies of North America and Europe. At first sight, the rising Christianity of the global South appears fundamentalist and deeply conservative. But at the same time these new Christians draw conclusions from scripture that are innovative, creative, and socially liberating, in their impact on social structures and gender relations. In fact, this Biblical enthusiasm is embraced by exactly those groups often portrayed as the victims of reactionary religion, particularly women, and a Biblically-rooted Christian feminism enjoys growing influence. Their fundamentalism does not deny or defy modernity, instead the Bible supplies a tool to cope with modernity, and to assist the most marginalized members of society. This, says Jenkins, is precisely the reason for Christianity's explosive growth. Many Southern churches take very seriously the supernatural world-view that pervades the Christian scriptures, with the recurrent themes of demons, possession, exorcism and spiritual healing. Yet readings that appear intellectually reactionary encourage believers to engage in far-reaching social activism. Across Africa, Asia, and Latin America, churches seek both deliverance and liberation--deliverance from evil supernatural forces, and liberation from oppressive worldly structures. Such examples challenge our conventional division of religion into conservative and liberal forms, and make nonsense of our concepts of "fundamentalism."--Publisher description.
Shall the fundamentalists win? -- Power in the book -- Old and new -- Poor and rich -- Good and evil -- Persecution and vindication -- Women and men -- North and south.
Includes bibliographical references (pages 201-238) and indexes.
Print version record.
Master record variable field(s) change: 082
Keywords: Christianity -- Forecasting; Christianity and culture; Christianity; Christianity and culture; RELIGION -- Christian Church -- History; RELIGION -- Christianity -- History; Christianity and culture; Christianity -- Forecasting; Electronic books